The Effects of E-commerce Adoption on Supply Chain Efficiency in Retail Businesses - Jan Jonsson; Erik Hemberg; Lars Nilsson (International Forum of Researchers and Lecturers, 2024)
This article explores the impact of e-commerce adoption on supply chain efficiency within retail businesses. The study utilizes a mixed-method approach to assess improvements in inventory management, order processing, and customer satisfaction following e-commerce integration. Results demonstrate that e-commerce adoption enhances supply chain efficiency, allowing retail businesses to reduce lead times, minimize stockouts, and meet consumer demands more effectively. The findings underscore the transformative potential of e-commerce for retail supply chains.